Effects of Nurse-Led Selfcare Interventions on Health Outcomes among People with Heart Failure (The Review of Diabetic Studies, 2024)
This study investigates the impact of nurse-led self-care interventions on health outcomes in patients with heart failure (HF), a condition characterized by the heart's inability to pump blood effectively, resulting in significant morbidity, mortality, and healthcare burdens. Given the complexities of HF management, including medication adherence and lifestyle modifications, effective self-care is crucial. However, many patients face challenges in self-care due to factors such as lack of knowledge, emotional distress, and insufficient support. This research highlights the pivotal role of nurses in providing education and support to empower patients, enhance health literacy, and foster engagement in self-management practices. Through comprehensive assessments, nurses can tailor interventions to meet individual needs, addressing barriers such as social determinants of health and mental health conditions. The study employs a robust evaluation framework encompassing clinical metrics, such as hospital readmission rates and changes in ejection fraction, alongside quality of life assessments using validated instruments like the Kansas City Cardiomyopathy Questionnaire. By analyzing these outcomes pre- and postintervention, the study aims to elucidate the effectiveness of nurse-led self-care strategies in improving health outcomes for HF patients. Furthermore, it emphasizes the importance of patient feedback and engagement in the design and implementation of interventions, recognizing that understanding patient barriers and incorporating digital health tools can enhance adherence to self-care practices. The findings are expected to contribute to the growing body of evidence supporting nurse-led interventions as a viable strategy to improve health outcomes in heart failure management, ultimately leading to reduced hospitalizations, enhanced quality of life, and better overall patient empowerment in managing their health. This research underscores the necessity for innovative, nurse-driven approaches to address the multifaceted challenges faced by heart failure patients, aiming to bridge the gap between clinical guidelines and personalized care.